1998
DOI: 10.1063/1.368087
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio molecular-orbital study on hydrogen-abstraction reactions at the growing surface of hydrogenated amorphous silicon

Abstract: Energy profiles have been evaluated by an ab initio molecular-orbital method for hydrogen-abstraction reactions from surface model compounds of growing hydrogenated amorphous silicon (a-Si:H) by a SiH3 radical, a presumed main precursor to a-Si:H, as well as by a hydrogen radical which should coexist in the silane plasma chemical vapor deposition. The activation energies calculated for these two reactions decrease as the cluster size of the film surface model SinH2n+2 increases from n=1 to n=4 to converge for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Though many efforts have been made to understand and control the chemical reactions involved in the CVD mechanism to produce better quality thin films, little is known about the initial steps of the mechanism of CVD. [22][23][24][25][26][27][28][29] Therefore, it would be interesting to investigate theoretically the initial steps of the CVD mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many efforts have been made to understand and control the chemical reactions involved in the CVD mechanism to produce better quality thin films, little is known about the initial steps of the mechanism of CVD. [22][23][24][25][26][27][28][29] Therefore, it would be interesting to investigate theoretically the initial steps of the CVD mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…These include decomposition temperature, concentration of source gas, substrate temperature, etc. , At lower temperatures, the decomposition of B 2 H 6 into BH 3 is more probable than the dissociation of either SiH 4 or H 2 because of the lower dissociation energy of B 2 H 6 . Thus, the interaction of BH 3 with SiH 4 might have a significant role in the initial steps of the CVD mechanism. Though many efforts have been made to understand and control the chemical reactions involved in the CVD mechanism to produce better quality thin films, little is known about the initial steps of the mechanism of CVD. Therefore, it would be interesting to investigate theoretically the initial steps of the CVD mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported a barrier of 0.239 eV for the mono-hydride and between 0.317 eV and 0.416 eV for the di-hydride configuration. Nakajima et al 19 used an ab initio molecular-orbital method to calculate the activation energy barrier for abstraction of H from Si n H 2nϩ2 (1рnр7) clusters. The activation energy barrier was between 0.28 and 0.46 eV, higher for smaller clusters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silica deposition from SiH 4 /O 2 mixtures has been reported to occur predominantly through only one type of intermediate species (SiO m H n with m and n having unique values), which is in agreement with a hydrogen elimination path lacking in gas-phase dehydrogenation reactions such as b1−b3. Neutral radicals are also known to play an important role in the growth and hydrogen elimination mechanisms involved in other CVD systems: e.g., hydrogen abstraction reactions in diamond , and silicon , CVD (with the application of different activation methods such as plasmas or hot filaments) and oxygen atom induced deposition of silica films in plasma-enhanced CVD from tetraethyl orthosilicate/O 2 mixtures. The specific surface mechanisms accounting for the hydrogen elimination process in our system, probably included in reactions d1 and d2, are beyond the scope of this work and would need extensive investigations at a fundamental level.…”
Section: Resultsmentioning
confidence: 99%